FEATURES OF ORGANIZING AN INCLUSIVE EDUCATIONAL PROCESS IN PRIMARY SCHOOL - Tyulpa, Tetyana (Sworld-Us Conference proceedings, 2025)
The article presents an analysis of the process of creating a favorable inclusive environment in primary school, which involves creating conditions for learning for students with special educational needs together with their peers, taking into account the